3.2: Invited Paper: Color E‐paper: Current Performance and Achievable Goals. (26th August 2021) - Henzen, Alex; Zhong, Benpeng; Liu, Linwei; Jiang, Hongwei; Zhou, Guofu
Abstract : In the search for acceptable reflective displays, electrofluidic / electrowetting displays have emerged as the leading technology for achieving high chromaticity gamut as well as fast switching and good reflectance. The prototypes shown demonstrate capabilities, but also have several issues that still need work. One of the most obvious areas is the spurious reflections from internal surfaces and refractive index steps. But also unwanted diffusion and absorption play a role Finally, maximizing the aperture is something that needs further development in order to promote the white state from "limit acceptable" to "top of class".